2018
DOI: 10.1016/j.cub.2018.08.044
|View full text |Cite
|
Sign up to set email alerts
|

A Human Polymorphism in CHRNA5 Is Linked to Relapse to Nicotine Seeking in Transgenic Rats

Abstract: Highlights d The nicotinic a5 subunit is necessary for the acquisition of nicotine-SA in rats d a5SNP rats (rs16969968 polymorphism) self-administer more nicotine at high doses d a5SNP rats exhibit higher nicotine-induced reinstatement of nicotine seeking d Activation of interpeduncular nucleus neurons by nicotine is reduced in a5SNP rats

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
68
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(71 citation statements)
references
References 59 publications
3
68
0
Order By: Relevance
“…It was confirmed by a recent study realized by Forget et al showing that transgenic rats expressing a human nicotinic receptor polymorphism selfadminister more nicotine at high doses and exhibit higher nicotine-induced reinstatement of nicotine seeking than wild type. This relapse is associated with reduced neuronal activity in the interpeduncular nucleus [51]. All these studies show the importance of the rs16969968, especially for early diagnosis of LC, and may provide potential targets for new therapies for smoking cessation interventions.…”
Section: Discussionmentioning
confidence: 80%
“…It was confirmed by a recent study realized by Forget et al showing that transgenic rats expressing a human nicotinic receptor polymorphism selfadminister more nicotine at high doses and exhibit higher nicotine-induced reinstatement of nicotine seeking than wild type. This relapse is associated with reduced neuronal activity in the interpeduncular nucleus [51]. All these studies show the importance of the rs16969968, especially for early diagnosis of LC, and may provide potential targets for new therapies for smoking cessation interventions.…”
Section: Discussionmentioning
confidence: 80%
“…; Forget et al. ). Genome‐wide association studies have indicated that single‐nucleotide polymorphisms (SNPs) within genes encoding nAChR subunits can substantially affect nAChR‐mediated smoking behavior in humans.…”
Section: Introductionmentioning
confidence: 97%
“…␣5 subunits are nearly 10-fold more abundant in IPN than in any other brain area (Forget et al, 2018), and ␣5 knockout mice do not exhibit nicotine withdrawal (Salas et al, 2009) or attenuated nicotine self-administration of aversive doses of nicotine (Fowler et al, 2011). Rats expressing an ␣5 sequence variant associated with human nicotine dependence and lung cancer show more facile relapse to nicotine-seeking behavior as well as an inverse correlation between IPN neuronal activity and relapse behavior (Forget et al, 2018). These results support our data demonstrating sensitized neuronal and nAChR activity in the IPN following exposure to nicotine, and point to ␣5-containing nAChRs as a possible therapeutic target for smoking cessation (Picciotto and Kenny, 2013).…”
mentioning
confidence: 93%
“…IPN components, especially ␣5-containing nAChRs, are emerging as key mediators of nicotine dependence-associated behaviors. ␣5 subunits are nearly 10-fold more abundant in IPN than in any other brain area (Forget et al, 2018), and ␣5 knockout mice do not exhibit nicotine withdrawal (Salas et al, 2009) or attenuated nicotine self-administration of aversive doses of nicotine (Fowler et al, 2011). Rats expressing an ␣5 sequence variant associated with human nicotine dependence and lung cancer show more facile relapse to nicotine-seeking behavior as well as an inverse correlation between IPN neuronal activity and relapse behavior (Forget et al, 2018).…”
mentioning
confidence: 99%